Investors’ confidence in the Malaysian stock market and religiosity during investment decisions - Jaiyeoba, Haruna Babatunde; Abideen, Adewale Abideen; Haron, Razali (IIUM Institute of Islamic Banking and Finance (IIiBF), 2019)
This study investigates investors’ confidence in the Malaysian stock market based on the notion that stocks are the best investment avenue for long-term investors, who can just buy and hold through the ups and downs of the market. Knowing about investors’ confidence in the Malaysian stock market is important because confidence in capital market is a critical driver of economic and financial fluctuations; in this case, investors would be willing to invest at prevailing prices if their confidence level is high. In fact, they would increase their holdings of risky investment by buying appropriate instruments in the marketplace if the confidence level is high. As such, the success of securities markets is particularly dependent on the investors’ confidence and as such, it has gained the interests of policymakers and academicians. In addition, this study also examines the role of investors’ religiosity during investment decisions. Religion affiliation is one of the contributing factors that influence the wealth accumulation and investors’ investment behaviour. Based on this, religion plays an important role during investors’ investment decisions, especially in Malaysia and other related countries. Therefore, this study has dual objectives, namely to investigate investors’ confidence in the Malaysian stock market, as well as their religiosity during investment decisions. To achieve these objectives, survey questionnaire was developed by the researchers and completed by 366 stock market investors, including fund managers and retail investors. Using several suitable analyses, we have concluded, though with caution, that stock market investors have confidence in the Malaysian stock market as the best investment avenue in the country. Moreover, this study has also shown that highly religious investors hold firmly to their religion guidelines when making investment decisions compared to other investors in the lowest category; more so, ethical businesses and being socially responsible are other factors found important to the investors before selecting company for investment reasons. As a result, discussions are made, implications are offered, and recommendations for future studies are discussed.